IMPLEMENTASI LOAD BALANCING METODE PER CONNECTION CLASSIFIER DAN FAILOVER RECURSIVE MENGGUNAKAN MIKROTIK - Bilal Magfa Ribhi Rahmat (AMIK Mitra Gama, 2022)
With the rapid development of technology, a company or agency must adapt systems that are evolving fast day by day. At PT Global Teknologi servisindo have problems faced with several problems due to complaints from employees who are constrained by a slow internet connection. Inadequate facilities such as devices to manage all internet connection systems and providers who are not yet able to accommodate the burden of internet lines. The implementation of load balancing with pcc and recursive failover methods enables internet connection and optimizes internet paths effectively. The device used is the Mikrotik RB1100ahx and to configure the load balancing and failover system using the Winbox software. The use of load balancing and failover can reduce internet paths so that there is no overload on the internet network. The results obtained by building a load balancing and failover system that maximizes internet connections properly and reduces overloads on internet lines, this proves that load balancing and failover are running well according to the configuration made.